Analisis Kandungan Alkohol pada Parfum yang Dibuat dari Bahan Sintetik dan Bahan Alam Menggunakan Metode Kromatografi Gas - Aditya Noviadi Rakhmatullah; Lisa Andina; Indra Syahfari; Didik Rio Pambudi (Jurnal Surya Medika (JSM), 2022)
The need for halal cosmetics around the world is currently still an interesting issue to continue to be discussed, considering that there are still many cosmetics that are suspected to contain haram ingredients in them. One of the cosmetic products that are often used is perfume. The purpose of this study was to identify the alcohol content in perfume products derived from natural and synthetic materials and to determine the alcohol content in these perfume products. In this study, the gas chromatography method was chosen because with this method the analysis process can be carried out quickly, more efficiently, with high resolution, sensitive, relatively simple, and inexpensive. The tests carried out include qualitative and quantitative tests. The results of the qualitative test showed that all the perfume samples tested showed positive results containing alcohol. While the results of the quantitative test for determining the alcohol content showed the results of samples D and E which were perfumes derived from synthetic materials containing alcohol with levels of 7.9% and 5.7%, respectively. Sample D contains the highest percentage of alcohol. Based on the fatwa from the MUI, cosmetics are allowed to contain fermented fruit alcohol with a level of less than 0.5%.